Evaluation of the reliability of the data generated by Next Generation Sequencing from artificially degraded DNA samples. (December 2015) - Carboni, I.; Fattorini, P.; Previderè, C.; Ciglieri, S. Sorçaburu; Iozzi, S.; Nutini, A.L.; Contini, E.; Pescucci, C.; Torricelli, F.; Ricci, U.
Abstract: NGS has the potential to be a promising technology for recovering genetic information from challenging specimens in forensic genetics. In order to understand the role of DNA damage on the outcome of NGS, we investigated the performance of ForenSeq™ DNA Signature kit, Illumina (in its pre-commercial version) on a set of in vitro degraded trial DNA samples. After DNA quantification by qPCR, duplicate analyses of the samples were carried out. The resulting molecular products were then sequenced by using MiSeq ® system (Illumina) and analyzed using ForenSeq™ Universal Analysis Software (Illumina). The coverage and error rate of the NGS data obtained from the degraded samples were compared to the ones gathered from the unmodified DNA. The NGS data showed that the ability of recovering genotypes and the frequency of analytical artifacts are strongly influenced by the degree of damage of the template. NGS was able to call 46–17% of the STR loci and 68–26% of the SNPs in the degraded samples. In addition, when the genotypes from the degraded samples were compared to the ones recovered from the unmodified control DNA, correct typing was achieved from 39 to 4% of the STRs and from 55 to 13% of the SNPs. These data show that NGS is a powerful method for gathering genetic data from samples which failed the conventional approaches, even if in this experiment the risk of mistyping seems not to be negligible (up to 2%).